Validation of a new method for the endoscopic measurement of post-bariatric gastric outlet using a standard guidewire: an observer agreement study - De Quadros, Luiz Gustavo (2017)
Background and aims: Between 10 and 20% of all patients undergoing bariatric surgery procedures regain weight secondary to a gastrojejunostomy enlargement. The aim of this study was to validate the interobserver agreement while measuring gastric outlet diameters using a new standard guidewire. Methods: We selected thirty-five videos of consecutive endoscopic procedures on patients undergoing esophagogastroduodenoscopy after a Roux-en-Y gastric bypass procedure. All videos were evaluated by four raters: two expert endoscopists and two trainees. We excluded videos having a slipped Fobi ring or a strictured gastric outlet. Anastomosis diameter was measured using a novel device with standardized markings on a guidewire (Hydra jagwire, Boston Scientific, Natick. MA) as well as the current gold standard defined as a calibrated endoscopic measuring instrument (Olympus America, Center Valley, PA). Results: We obtained 272 measurements of the gastric outlet. Overall agreement measured through intra-class correlation coefficients for the gold standard was 0.84 (p < 0.01) and 0.83 (p < 0.01) for the new guidewire. Agreement among experts was 0.699 (p < 0.01), while among trainees it was 0.822 (p < 0.01). Conclusion: The new guidewire demonstrated a high degree of observer reliability, also presenting similar results between expert endoscopists and trainees.